Pengembangan Modul Pembelajaran Biologi Berbasis Keterampilan Berpikir Kritis Siswa Kelas X SMK Negeri 1 Gunungsitoli Alo’oa Tahun Pembelajaran 2024/2025 - Tri Jon Ade Irman Laoli; Dirikan Hati Daeli; Jun Mestika Fati Hia (Program Studi Pendidikan Biologi - Universitas Nias, 2025)
Low critical thinking skills and student learning outcomes are major problems in biology learning, exacerbated by the lack of learning modules that facilitate independent learning. This study aims to develop a biology module based on critical thinking skills on ecosystem material that is suitable for use and to determine student responses to the module. This Research and Development (R&D) study refers to the Borg and Gall model modified into nine stages, starting from preliminary studies to final product refinement. Quantitative and qualitative data were collected through validation sheets by four validators (material experts, subject teachers, linguists, and design experts), a module feasibility questionnaire, and response questionnaires from 34 grade X students of SMK Negeri 1 Gunungsitoli Alo'oa. The development results showed that the module achieved a validity level of 100% from all validators. Large-scale trials by students showed a feasibility level of 95% (very strong category), and student responses reached 82% (very strong category). This critical thinking-based biology module proved very suitable for use in learning to support student learning independence.